Structure of quinoline-4-carboxaldehyde-2,4-dinitrophenyl-N methylhydrazone - Isik, S; Aygun, M; Ocal, N; Nawaz, TM (MARCEL DEKKER INC, 1998)
The crystal structure of the title compound, C17H13N5O4, has been determined by single crystal x-ray diffraction at room temperature. The molecule is not planar, with dihedral angles of 7.2(1)degrees between the quinoline ring and N-methylhydrazone group, and 17.45(2)degrees between the N-methylhydrazone group and the phenyl ring. The crystal parameters of this compound are as follows: monoclinic P 2 1/n, a=9.525(2)Angstrom, b=15.192(2)Angstrom, c=11.302(2)degrees, beta = 94.722(3)degrees V = 1629.8(6) Angstrom(3), Z = 4, Dr = 1.432 g/cm(3), F(000)= 728, lambda (MoK alpha)= 0.71070 Angstrom, CI = 0.106 mm(-1), R-int = 0.017. The structure was solved by SHELXS-86 and refined by SHELXL-93. R = 0.07 for 2438 observed reflections with 1 > 2 sigma (I).
Keywords: Spectroscopy